2011
DOI: 10.1111/j.1600-0838.2011.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Guided imagery to improve functional outcomes post‐anterior cruciate ligament repair: randomized‐controlled pilot trial

Abstract: Imagery can improve functional outcomes post-anterior cruciate ligament repair (ACLR). Research is needed to investigate potential mechanisms for this effect. The aim of this study was to (a) evaluate the effectiveness of an imagery intervention to improve functional outcomes post-ACLR, and (b) explore potential mechanisms. A randomizedcontrolled pilot trial was conducted. Participants were randomized to guided imagery and standard rehabilitation or standard rehabilitation alone (control). The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 15 publications
1
62
0
11
Order By: Relevance
“…Four relevant studies 5,8,10,11 were located and categorized, as shown in Table 1 (based on Levels of Evidence, Centre for Evidence Based Medicine, 2011).…”
Section: Results Of Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Four relevant studies 5,8,10,11 were located and categorized, as shown in Table 1 (based on Levels of Evidence, Centre for Evidence Based Medicine, 2011).…”
Section: Results Of Searchmentioning
confidence: 99%
“…Imagery is defined as a process of performing a skill in one's mind using the senses (touch, feel, smell, vision, etc) without any overt actions. 8 Incorporating a therapeutic intervention that targets the psychological effects on an athletes' ability to return to sport is necessary to assure that the patient is both physically and mentally prepared to return to activity. Therefore, the purpose of the critically appraised topic was to determine if imagery training in combination with standard physical therapy is a suitable option to reduce the fear of reinjury and pain perception among first-time anterior cruciate ligament reconstruction (ACLR) patients.…”
Section: Clinical Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Existing related research has examined different types of interventions, such as instructor-led strategies, and measured other types of variables, such as flexibility or quality of life [50,51]. Given the potential economic, physical, social, and psychological benefits from the implementation of low cost, relatively simple cognitive strategies, such as those included in the current review, it appears justifiable to suggest research in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…The only imagery intervention study considering self-efficacy was recently conducted by Maddison et al (2011). The aim of this study was to evaluate the effectiveness of a guided imagery and relaxation program on improving functional outcomes post-anterior cruciate ligament repair delivered over nine individual sessions as an adjuvant treatment to standard rehabilitation.…”
mentioning
confidence: 99%